Význam koučovacej pozície kresťanského kouča pre kouča a klienta = The Significance of Coaching Position of a Christian Coach to Coaches and Clients - Králová, Eva (Vilnius: Mykolas Romeris Universitetas)
Through the definitions of life coaching and Christian coaching, with the clarification of what makes life coaching Christian, the authoress focuses primarily on the possible benefits of coaching position of a Christian coach during coaching dialogue for a coach. Christopher McCluskey defines Christian coaching as "a way of helping people find God's healing and respecting vision for their lives and learn to live accordingly".
Keywords: coach chrześcijański; coachingowa pozycja chrześcijańskiego coacha; rozmowa coachingowa; mocne pytania; Christian coach; Coaching position of a Christian coach; powerful questions